THE EFFECT OF USING SCIENTIFIC APPROACH ON STUDENTSâ€™ VOCABULARY ACHIEVEMENT AT GRADE EIGHT OF SMP MUHAMMADIYAH KENDARI - Demaulid, Demaulid; Siam, Siam; Fatmawati, Wa Ode (Universitas Halu Oleo, 2020)
This study was conducted to investigate the effect of using Scientifics Approach on Studentsâ€™ vocabulary achievement at grade eight of SMP Muhammadiyah Kendari. The research question of this study was â€œIs there any significant effect in using of Scientific Approach to increase the studentsâ€™ vocabulary achievement at grade eight of SMP Muhammadiyah Kendari?â€ The objective of the study was to find out data and information whether there is a significant effect in using of Scientific Approach to increase the studentsâ€™ vocabulary achievement at grade eight of SMP Muhammadiyah Kendari. The design of study was a pre-experimental design. The sample of this study was taken by using random sampling which consisted of 30 students. The instrument of this study was vocabulary test which consisted 40 items. The result of the study showed that there was a significant effect in teaching vocabulary through the use of Scientific Approach at grade eight of SMP Muhammadiyah Kendari. The average of studentsâ€™ vocabulary achievement before using Scientific Approach was 4.99 which is in low category. Meanwhile, the studentsâ€™ vocabulary achievement after using Scientific Approach was 7.59 which is in high category. The result of hypothesis testing proves that t-test = 25.36 was higher than t-table = 2.04. This finding shows that in teaching vocabulary by using Scientific Approach improve studentsâ€™ vocabulary achievement at grade eight of SMP Muhammadiyah Kendari.